Almost identical but still treated differently: hiring discrimination against foreign-born and domestic-born minorities - Susanne Veit; Lex Thijsen (Journal of Ethnic and Migration Studies, 2019)
Focusing on birthplace (foreign vs. domestic) and origin group (European vs. Middle Eastern or African), this article examines the effects of cultural distance signals on discrimination against ethnic minority job applicants. Drawing on a cross-nationally harmonised correspondence test (N0.167em=0.167em5780), we investigate how employers in five Western European destination countries (Germany, the Netherlands, Norway, Spain, and the U.K.) respond to job applications from majority and minority group members, with minority job applicants being either very similar (domestic-born and/or European origin) to the majority population or rather different (foreign-born and/or Middle Eastern/African). Our results are generally consistent with taste-based discrimination theory. Employers pay attention to signals of cultural distance, which results in particularly high levels of discrimination against foreign-born minorities and against minorities originating from Middle Eastern and African countries. Although origin group has a stronger effect on employer responses than birthplace, they jointly exert an additive effect. This results in particularly low labour market chances for foreign-born minorities of Middle Eastern and African origin. Separate country analyses, however, reveal important country differences, both with respect to the size of the minority penalty and the joint effect of birthplace and origin group.
Keywords: 330; correspondence test; taste-based discrimination; birthplace; origin group; cultural distance